Approaching Winter : Poems - Skloot, Floyd (Book collections on Project MUSE., 2015)
Floyd Skloot's seven previous poetry collections include The End of Dreams, a finalist for the Paterson Poetry Prize, and The Snow's Music. His work has won three Pushcart Prizes and the PEN USA Literary Award in Creative Nonfiction. He lives in Portland, Oregon.